2017
DOI: 10.18632/oncotarget.15343
|View full text |Cite|
|
Sign up to set email alerts
|

Exclusive destruction of mitotic spindles in human cancer cells

Abstract: We identified target proteins modified by phenanthrenes that cause exclusive eradication of human cancer cells. The cytotoxic activity of the phenanthrenes in a variety of human cancer cells is attributed by these findings to post translational modifications of NuMA and kinesins HSET/kifC1 and kif18A. Their activity prevented the binding of NuMA to α-tubulin and kinesins in human cancer cells, and caused aberrant spindles. The most efficient cytotoxic activity of the phenanthridine PJ34, caused significantly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 45 publications
(126 reference statements)
5
46
0
Order By: Relevance
“…In these experiments PJ34 (60 mg/kg) was injected IP after the tumors reached a volume >100 mm 3 . PJ34 injected daily for 14 days efficiently suppressed tumor growth [31].…”
Section: Pj34 Causes Eradication Of Human Cancer Cells In Xenograftsmentioning
confidence: 93%
See 3 more Smart Citations
“…In these experiments PJ34 (60 mg/kg) was injected IP after the tumors reached a volume >100 mm 3 . PJ34 injected daily for 14 days efficiently suppressed tumor growth [31].…”
Section: Pj34 Causes Eradication Of Human Cancer Cells In Xenograftsmentioning
confidence: 93%
“…It was observed that apart from PARP inhibition, some of these molecules target a variety of kinases implicated in signal transduction pathways in both healthy and malignant cells [27]. Unexpectedly, this research also disclosed that a group of phenanthrene derivatives acting as PARP inhibitors, exclusively kill human cancer cells without affecting benign cells [28][29][30][31][32]. Unlike other PARP inhibitors, these small molecules exclusively eradicated a variety of human cancer cells without affecting proliferating and non-proliferating healthy somatic cells.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…PolyADP-ribosylation of TNKS1 may contribute to spindle bipolarity by providing a static matrix, anchoring microtubule-associated motor and spindle proteins [ 124 ]. A second PARP inhibitor, PJ-34, is currently undergoing pre-clinical trials and is known to induce distorted multipolar spindles and to disrupt bipolar clustering of extra centrosomes resulting in mitotic catastrophe and cell death, an effect exclusively eradicating cancer cells harbouring CA without affecting normal cell proliferation [ 124 , 132 , 150 ]. AZ0108 and PJ-34 showed better centrosome de-clustering abilities, compared to isoquinolinone-derived PARP inhibitors Tiq-A and Phen (phenanthrene) [ 124 , 151 ] ( Table 3 ).…”
Section: Small Molecule Inhibitors Targeted At the Chromosomal Levmentioning
confidence: 99%